O Discurso Motivacional Empresarial e a Construção Ideológica da Subjetividade - Preussler, Cibelle Cristina (2013)
The theme of this research is the Motivational Speech of the business sphere. Our professional experiences provided us a constant contact with the genres Motivational Lecture and Business Paradicdatic Manual, leading, consequently, to certain concerns that culminated in the realization of a systematic study of this subject, which had the aim of investigating the contradictions of Motivational Speech in the business sphere, enabling, thus, an understanding of how the linguistic-ideological sign reflects and refracts reality, being, at the same time, transformd by it. In search of an understanding for this process, we adopted the interactionist perspective of language, considering the statements as being part of a chain of past, present and future sayings that interact dialogically. This study was held based on the theory of Mikhail Bakhtin and his Circle (1976, 1981, 2004, 2010) by choosing a methodology which prioritized the study of statements of the business sphere by linking them with their determining socio-economic structure as well as the particularities of its sphere of ideological production. The Motivational Speech, as an element that contributes to the ideological construction of human subjectivity, has the aim of molding a successful human being, who is fully dedicated to his work, and that is always looking for professional recognition. The ideology of motivation teaches that working is a virtue, that professional success dignifies men and that their happiness and fulfillment can only be achieved through their total dedication and loyalty to companies, thus acting as a set of rules that hides behind an apparent rational coherence, but in the background is made up of silences that legitimize the ideology of the ruling class.